EVALUASI BUDAYA KERJA ORGANISASI SEKTOR PUBLIK MELALUI PENDEKATAN COMPETING VALUES FRAMEWORK - Bambang Aditio; Afriva Khaidir; M. Fachri Adnan (PT. Saha Kreasi Indonesia, 2026)
Work culture is a key determinant of bureaucratic reform success, yet its evaluation in public sector organizations often relies on instruments developed for private-sector contexts without accounting for distinct institutional characteristics of government. This conceptual article explains the rationale for using the Competing Values Framework (CVF) to evaluate public sector work culture, outlines fundamental differences between measuring work culture in the public versus private sectors, and discusses the implications of a dominant culture type for innovation capacity and bureaucratic reform. Through narrative-integrative synthesis of Scopus-indexed and reputable peer-reviewed literature, the article shows that CVF's strength lies in combining the parsimony of two value dimensions (flexibility-stability and internal-external focus) with four psychometrically validated culture archetypes (Clan, Adhocracy, Market, Hierarchy). The synthesized evidence shows public organizations consistently skew toward Hierarchy culture with comparatively low Adhocracy scores, a pattern aligned with bureaucratic accountability demands but associated with weaker outcome orientation and innovation capacity. The article recommends an ambidextrous strategy that preserves Hierarchy's control function while cultivating Adhocracy and Clan elements through authentic leadership and employee psychological empowerment.